The Influence Of Quality Of Work Life And Employee Engagement On Organizational Citizenship Behavior(OCB)Mediated By Job Satisfaction(Study Of KPP Pratama Semarang Gayamsari Employees) - Ana Martanti; Indarto Indarto; Yuli Budiati (Jurnal Scientia, 2024)
Among the goals of the study is to examine how employee involvement and quality of work life affect KPP Pratama Semarang Gayamsari employees' job satisfaction. to examine how employee engagement, job happiness, and quality of work life affect KPP Pratama Semarang Gayamsari employees' organizational citizenship behavior (OCB). To examine how job satisfaction affects KPP Pratama Semarang Gayamsari employees' organizational citizenship behavior (OCB), as well as how employee engagement and quality of work life influence it. The study's participants comprised 87 employees of KPP Pratama Semarang Gayamsari. The census sampling technique, which includes all 87 respondents in its sample, was used for the sampling process. Primary data in the form of a questionnaire is what is used. Partial regression analysis (Partial Least Square/PLS) is used in the data analysis process. According to study findings, job satisfaction is positively and significantly impacted by one's work life quality. Job happiness is positively and significantly impacted by employee engagement. Organizational Citizenship Behavior is positively and significantly impacted by work life quality (OCB). Organizational Citizenship Behavior is positively and significantly impacted by employee engagement (OCB). Organizational Citizenship Behavior (OCB) is positively and significantly impacted by job satisfaction. The impact of work life quality on organizational citizenship behavior (OCB) is not mitigated by job satisfaction. Work satisfaction acts as a mediator between employee engagement and Organizational Citizenship Behavior (OCB)